The stress response of Ragusano donkey (Equus asinus) to different semen collection techniques. - Fazio E; Ferlazzo A.; Cristarella S.; Medica P.; Marino G.; Quartuccio M. (Polish Academy of Sciences, 2017)
The aim of the present study was to characterize the stress response of donkeys to different semen collection techniques, comparing the physiological patterns of hormonal (adrenocorticotropic hormone: ACTH, cortisol) and biochemical variables (creatinine, total protein, urea, aspartate aminotransferase: AST, alanine aminotransferase: ALT), and routine seminal parameters and sexual behaviour. Twenty two healthy Ragusano donkeys were used and were randomly assigned to one of 2 groups based on different semen collection techniques. Group A was designated as the experimental group and included 16 donkeys submitted to semen collection by an artificial vagina (AV) "on the ground"; group B was designated as the control group, and included 6 donkeys submitted to semen collection by AV during the mount. The semen collection was performed in October, once a day for 10 consecutive days. Blood samples were collected in baseline conditions, before the onset of the treatments and within 30 min after, from the jugular vein of each subject. Two-way ANOVA showed a significant effect of semen collection technique and time points in group A for ACTH (p=0.0084), cortisol (p=0.0004) and creatinine (p=0.0131), with lower values after semen collection than before. A significant effect of semen collection technique and time points in group B for ACTH (p<0.0001) and cortisol (p<0.0001) was observed, with higher values after semen collection than before. The comparison between groups A and B values over different time points showed a significant effect after semen collection for ACTH (p<0.0001), cortisol (p<0.0001) and creatinine (p<0.0001), with the highest values in group B. This study provides the physiological evidence that semen collection on the ground in healthy donkeys could be used as an alternative strategy to induce a positive animal approach and economical advantages.
Keywords: Male; Semen Analysis; Semen; Stress, Physiological; Sperm Motility; Animals; Equidae; donkey, semen collection techniques, ACTH, cortisol, biochemical variables; Specimen Handling